Ruptured cysticercosis may mimic deep vein thrombosis - Nagabhushanarao, Bhavana Venkata; Raman, Bhavana Venkata Satya (International Journal of Research in Medical Sciences, 2018)
In clinical practice, we come across many a times various cystic and firm nodular swellings over various parts of the human body. We opt for fine needle aspiration cytology examination of the lesion to determine the aetiology. If it happens to be parasitic cyst it may rupture and produce systemic or local hypersensitivity reaction. Sometime such anaphylactic reaction may endanger the life of the patient. Here we present a case of ruptured cysticercosis mimicking a deep vein thrombosis. We discussed its presentation, diagnosis and management.